2021
DOI: 10.34117/bjdv7n10-426
|View full text |Cite
|
Sign up to set email alerts
|

Uso de microminerais complexados na redução de lesões de casco em reprodutoras suínas/ Use of complexed trace minerals to improve claw lesions in swine sows

Abstract: As lesões nos cascos em porcas têm alta prevalência no Brasil e resultam em perdas no desempenho produtivo e econômico da produção, além de comprometer o bem-estar dos animais. Vários fatores estão envolvidos em seu desenvolvimento, incluindo o tipo de alojamento, os manejos, os aspectos nutricionais e genéticos. O objetivo deste estudo foi avaliar o efeito dos minerais Zinco, Cobre, Manganês, Cromo e Selênio complexoaminoácidos na prevalência de lesões nos cascos de matrizes suínas em uma granja localizada no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
2
0
0
Order By: Relevance
“…The prevalence rates of volar surface lesions, wall lesions, and toe overgrowth were 93.7%, 89.6%, and 84.8%, respectively (Table 2). Earlier assessments and cross-sectional studies on claw lesions in sows have reported a prevalence ranging between 60-100% (Anil et al, 2007;Pluym et al, 2011;Díaz et al, 2014;Lisgara et al, 2015;Cerutti et al, 2021;Skampardonis et al, 2022), which is in agreement with the findings of this study (99.1%). Managers must be aware of this prevalence and the specific situation on their farms, as claw lesions substantially impact animal welfare, reproductive performance, sow longevity, and offspring performance (Olsson et al, 2016).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The prevalence rates of volar surface lesions, wall lesions, and toe overgrowth were 93.7%, 89.6%, and 84.8%, respectively (Table 2). Earlier assessments and cross-sectional studies on claw lesions in sows have reported a prevalence ranging between 60-100% (Anil et al, 2007;Pluym et al, 2011;Díaz et al, 2014;Lisgara et al, 2015;Cerutti et al, 2021;Skampardonis et al, 2022), which is in agreement with the findings of this study (99.1%). Managers must be aware of this prevalence and the specific situation on their farms, as claw lesions substantially impact animal welfare, reproductive performance, sow longevity, and offspring performance (Olsson et al, 2016).…”
Section: Resultssupporting
confidence: 93%
“…of prevalence demonstrated that HOE was the most common lesion (89.9%), followed by CWH (86.4%), T (74.8%), DC (67.6%), WL (48.6%), CWV (32.6%), and HSC (15.7%) (Table 2). The high occurrence of HOE (89.9%) was consistent with other studies that reported high prevalence of HOE in sows in Brazil (Cerutti et al, 2021), Greece (Lisgara et al, 2015), Japan (Sasaki et al, 2015), and Canada (Grégoire et al, 2013). Heel lesions are normally a consequence of chronic weight overload or friction with an uneven or abrasive floor, which results in hyperkeratinization of the epidermis, forming a callus.…”
Section: Discussionsupporting
confidence: 88%